An Outcome Study of Anterior Cervical Discectomy and Fusion among Iranian Population. (18th August 2016) - Haghnegahdar, Ali; Sedighi, Mahsa
Abstract : Background and Aim . First-line treatment strategy for managing cervical disc herniation is conservative measures. In some cases, surgery is indicated either due to signs/symptoms of severe/progressive neurological deficits, or because of persistence of radicular pain despite 12 weeks of conservative treatment. Success for treatment of cervical disc herniation using ACDF has been successfully reported in the literature. We aim to determine the outcome of ACDF in treatment of cervical disc herniation among Iranians. Methods and Materials/Patients . In a retrospective cohort study, we evaluated 68 patients who had undergone ACDF for cervical disc herniation from March 2006 to March 2011. Outcome tools were as follows: (1) study-designed questionnaire that addressed residual and/or new complaints and subjective satisfaction with the operation; (2) recent (one week prior to the interview) postoperative VAS for neck and upper extremity radicular pain; (3) Japanese Orthopaedic Association Myelopathy Evaluation Questionnaire (JOACMEQ) (standard Persian version); and (4) follow-up cervical Magnetic Resonance Imaging (MRI) and lateral X-ray. Results . With mean follow-up time of 52.93 (months) ± 31.89 SD (range: 13–131 months), we had success rates with regard to ΔVAS for neck and radicular pain of 88.2% and 89.7%, respectively. Except QOL functional score of JOAMEQ, 100% success rate for the other 4 functional scores of JOAMEQ was achieved. Conclusion . ACDF is a successful surgical technique for the management of cervical disc herniation among Iranian population.